Penambahan Ekstrak Daun Benalu Kelapa Sawit (Ficus heteropluera Blume) Pada Pembuatan Membran Dan Uji Antibakteri Escherichia coli - Yola Suryani; Fitra Perdana; Jufrizal Syahri (Photon: Jurnal Sain dan Kesehatan, 2024)
Palm mistletoe leaves (Ficus heteropluera Blume) are a plant that is effective as an antibacterial medicine. Palm mistletoe leaves contain antibacterial compounds such as flavonoids, tannins, sapoins and phenolics. One alternative to reduce fouling is adding an anti-bifouling agent to the membrane. This research aims to determine the phytochemical test on oil palm mistletoe leaf extract, to see the antibacterial inhibition zone of Escherichia coli and determine the characteristics of thickness and biodegradation, as well as the antibiofouling properties of natural ingredients, namely oil palm mistletoe leaves. The addition of palm mistletoe leaf extract had concentrations of (4:0), (3.96:0.04), and (3.92:0.08) grams. For the antibacterial results obtained by adding a membrane to the additive, namely palm mistletoe leaves, namely variation 1, has an average diameter of 4.73 mm, 4.3 mm and 4.33 mm. The positive control concentration had an average diameter of 38.3 mm. In variation 2 the measurement results do not show the existence of an inhibition zone. The measurement results of the positive control had an average diameter of 38.367 mm. For membrane thickness testing, namely 0.03 mm, 0.06 mm, and 0.06 mm, and the highest biodegradation test was found in the variation of adding 0.08 gram extract, namely 56% and the lowest biodegradation value was in the variation of adding 0.04 gram extract namely 35%.